Fatal flaws? Investigating the effects of machine translation errors on audience reception in the audiovisual context. - Qiu, Juerong; Pym, Anthony (Perspectives: Studies in Translatology, 2025)
This study reports on an experiment where machine translation errors in subtitling are evaluated from the perspective of nine viewers who did not know the source language and seven viewers who were studying the source language. Screen recordings, think-aloud protocols, comprehension tests, and interviews were employed to explore participants' responses and reactions to erroneous subtitles and to investigate how specific errors impacted comprehension and immersion in the viewing experience. The analysis identifies which errors were most noticed and to what extent those errors affected viewers' trust in the subtitles. Errors causing significant misunderstanding and distrust are initially considered 'fatal', as they may halt viewer immersion and prompt disengagement from the audiovisual product. However, the findings highlight a remarkable tolerance of the uncertainty that results from errors, as viewers filter out misinformation or draw on other sources of information to construe and rectify their interpretations. This tolerance is explained in terms of a general trade-off with the enjoyment of the viewing experience, which varies in accordance with the viewer's knowledge of the source language.